An analysis on the aftermath of Lahad Datu incursion / Siti Nur Azilayati Rahmah Raman and Mohd Adnan Hashim - RamanRaman, Siti Nur Azilayati Rahmah; Hashim, Mohd Adnan (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2020)
The 2013 Lahad Datu incursion has steered the establishment security zones by the Malaysian government aimed at securing the safety of Sabah’s eastern sea border. These are the Eastern Sabah Security Command (ESSCOM) and the Eastern Sabah Security Zone (ESSZONE) comprising a total of 10 districts. The question that arise is how effective is the security of ESSCOM in ensuring the safety of citizens living in ESSZONE since there are still occurrences of kidnapping especially with the recent case of kidnapping in Tambisan of which the Abu Sayyaf group from southern Philippines were said to be the suspects. This study seeks to investigate the awareness of residents living in the east coast of Sabah ESSCOM towards the accomplishments of the authorities in securing the safety of Sabah’s eastern seaboard. Additionally, it is aimed at exploring the security issues relating to the safety of the said seaboard. Besides this, this study also intends to identify security improvements with regards to the safety of the area. Data for the study was gathered via in-depth interviews with selected participants by using purposive sampling. The researchers utilised thematic analysis and computing applications made for qualitative research, the Atlas.ti for data analyses process. Results of the study indicate that ESSCOM is a relevant organization to protect the east coast of Sabah. Readers can gain a lot of knowledge from the various summarised opinions and comments made by participants, in relation to the threats and challenges in securing safety as well as ways of security improvements on the east coast of Sabah.